Decision Support System Design for Wedding Organizer Tradeshow Selection using AHP and TOPSIS - Rayinda Pramuditya Soesanto; Afrin Fauzya Rizana (International Journal of Innovation in Enterprise System, 2021)
Wedding organizers, as one of the creative industries, often participate in a trade show as one of themarketing mediums. Many wedding-related trades show events are held every year. But the cost toparticipate in one trade show event is quite expensive and increases from time to time. Thus, beforedeciding to participate in a trade show, it is important to evaluate whether the trade show events arerecommended to join or not. The purpose of this study is to design a decision support system thatwill help the wedding organizer to decide their participation in a trade show. The decision modelwas constructed using AHP and TOPSIS methods. There are seven factors considered in the model,i.e., tradeshow location, reputation and professionalism of the organizer, cost estimation, trade showprestige, tenant reputation, time of the event, the attractiveness of the event. By using the AHPmethod, the priority weight of each factor was calculated. Moreover, the weight obtained will beused in developing a decision model combined with the TOPSIS method. The decision supportsystem was developed afterward by using the SCRUM method. The feature of the system isdiscussed in the paper